Low serum zinc levels in patients undergoing coronary angiography correlate with immune activation and inflammation - Murr, Christian; März, Winfried (Journal of trace elements in medicine and biology, 2012)
Introduction: Low serum zinc concentrations are associated with adverse outcomes. To explain this phenomenon we aimed to investigate whether low zinc levels are related to immune activation, renal function and coronary artery disease (CAD). Methods: Serum concentrations of zinc and the immune activation markers neopterin and C-reactive protein (CRP) were measured in 2048 patients derived from the LUdwigshafen RIsk and Cardiovascular Health (LURIC) study, a cohort study among patients referred for coronary angiography. Results: Zinc concentrations did not differ between patients with CAD (mean±SD: 13.3±2.4μmol/L) and controls (13.3±2.2μmol/L; Welch's t test: p=n.s.) but CAD patients had higher neopterin (8.6±7.4nmol/L) and CRP (9.7±19.6mg/L) concentrations compared to controls (neopterin: 7.5±4.8nmol/L, p=0.0005; CRP: 5.5±10.0mg/L, p<0.0001). There was an inverse correlation between serum zinc concentrations and neopterin (Spearman's rank correlation: rs=−0.222) and CRP (rs=−0.166; both p<0.0001) concentrations. Conclusions: Our results indicate increased inflammatory processes in patients with low zinc levels. Further studies should clarify whether inflammation related processes such as renal wasting contribute to zinc deficiency and underlie the adverse health consequences of low serum zinc levels.
Gesehen am 29.08.2018